Rise of China : threat or opportunity - Agarwala, Ramgopal (New Delhi, 2002)
In recent years, the rise of China is a much talked about topic. Some believed that China's rapid growth is a myth perpetrated by government propaganda. Many others thought that the lack of democracy and the unfinished nature of reforms under China's "socialist market economy" would lead to an implosion as in the erstwhile Soviet Union. China has so far proven them wrong. There is now very little doubt that China has stood up and will be a dominating factor in Asia and the world during the twenty-first century. Many in Asia are now getting reconciled to China's rise but they now see as a threat. In this book Dr. Ramgopal Agarwala argues that even after allowing for weaknesses on China's statistics. China represents the most impressive and, because of its size, the most important development success story in the world history. Increasingly, 'look east' will mean looking to China. Within a generation China is likely to become the largest economy in the world and in that position it has much to contribute to developed and developing countries in terms of trade and investment and above all, in terms of ideas on development. This potential can, however, be realized only if the world integrates China into the world development community as an important member. If, however, the world continues to treat her as a threat, it will become one.
Keywords: International relations